ACCELERATING EXPANSION OF DIGITALIZED HIGHER EDUCATION SYSTEMS FOR CREATING BETTER LEARNING CONDITIONS WORLDWIDE - Akhmadbek Bakhtiyorov (Zeta Repository, 2023)
The dramatic growth in digitalization made youth to be surrounded with technological advancements, hence they want these technologies being used in everywhere as they understand them well. This thought is related to classrooms as well, students are willing to have more digitalized classes and creative approach of their instructors, especially at universities this is broadly expanded as undergraduates are aware of using latest innovations.